2019
DOI: 10.12659/msm.915814
|View full text |Cite
|
Sign up to set email alerts
|

Human β-Defensin-2 Improves Hyperoxia-Induced Lung Structural and Functional Injury in Neonatal Rats

Abstract: Background Bronchopulmonary dysplasia (BPD) is a major complication of extreme prematurity, characterized by alveolar simplification and pulmonary malfunction. Hyperoxia-induced lung injury in neonatal rats has been used as a model of BPD, as indicated by lung architectural change and alveolar simplification that resembles clinical feature of BPD. β-defensin-2 (BD2) plays an important role in lung diseases by inhibiting inflammation response. However, little is known about its role in BPD. The aim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…Hyperoxia-induced lung injury in newborn rats has long been used as a model of BPD (5,24). Previous studies have observed lung function to be remarkably impaired in hyperoxia-induced BPD with an abnormal increase in airway resistance and a decrease in dynamic lung compliance (25,26). In the present study, decreased lung function was also observed in newborn rats under hyperoxia exposure.…”
Section: Tet Inhibited Nf-κb and Erk1/2 Signaling Pathway In Newborn ...supporting
confidence: 66%
“…Hyperoxia-induced lung injury in newborn rats has long been used as a model of BPD (5,24). Previous studies have observed lung function to be remarkably impaired in hyperoxia-induced BPD with an abnormal increase in airway resistance and a decrease in dynamic lung compliance (25,26). In the present study, decreased lung function was also observed in newborn rats under hyperoxia exposure.…”
Section: Tet Inhibited Nf-κb and Erk1/2 Signaling Pathway In Newborn ...supporting
confidence: 66%
“…Recently, scholars in various fields tend to use gene overexpression technology to explore the mechanism of β-defensin regulating cancer diseases, species including human [ 25 , 26 ], pig [ 27 , 28 ], mice [ 29 , 30 ], etc. Similarly, RNAi technology is also increasingly used in gene functional analysis [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to the fact that hyperoxia can lead to excessive accumulation of reactive oxygen species in the body, promote the inflammatory factors expression, such as TNF-α, IL-1 hormone and IL-6 in the lung, and activate related pathways. Celecoxib can significantly inhibit pulmonary inflammatory factors expression (10).…”
Section: Comparison Of the Levels Of Inflammatory Factors In Lung Tis...mentioning
confidence: 99%